Ensaios sobre a dinâmica em finanças - Dana, Samy (2008)
This thesis is divided in two chapters. The first chapter entitled 'The Dynamics of the Dynamic Hedging' derives an optimal hedging ratio in a dynamic discrete-time stochastic setting allowing for margin requirements. Then, it empirically analyzes the dynamics of the hedging strategy in terms of wealth volatility by comparing alternative estimation methods. Besides considering margin accounts empirically, we also innovate by varying the out-of-sample hedging horizon for a representative investor from 10 to 127 days and evaluate the impact of the time horizon on the hedging efficiency. The second chapter entitled 'The impact of ETS market on the futures prices of electricity or Kyoto 220 volts: Fast and Furious' addresses the economic impact of the carbon allowance market in European Emission Trading Scheme (ETS) on the futures market of electricity and gas prices. We also analyze the dynamics relationship among these markets with coal and natural gas futures markets.